The efficacy and adverse events of conventional and second-generation androgen receptor inhibitors for castration-resistant prostate cancer: A network meta-analysis - Zhang, Xianlu; Zhang, Gejun; Wang, Jianfeng; Bi, Jianbin (Frontiers in Endocrinology, 2023)
Background: Second-generation androgen receptor inhibitors (ARIs) have been developed and approved for treating castration-resistant prostate cancer (CRPC). There is a lack of direct comparison of the therapeutic effects and adverse events between the conventional ARI (bicalutamide) and three second-generation ARIs (enzalutamide, apalutamide and darolutamide). Methods: Our network meta-analysis evaluated therapeutic effects and adverse events of the conventional ARI (bicalutamide) and the second-generation ARIs in treating CRPC. We systematically searched the Pubmed, Cochrane library and Embase databases for studies published until October 2022 and only randomized clinical trials (RCTs) were included. The progression-free survival, prostate-specific antigen (PSA) progression-free survival, overall survival (PFS/PSA-PFS/OS), PSA response rate and relative adverse events (AEs) of CRPC patients were collected and synthesized. We then performed subgroup analysis. The non-metastatic and metastatic CRPC (nm/mCRPC) observations were analyzed separately. Data analyses were performed using R software (4.2.1) based on Bayesian framework. Results: 6,993 subjects from seven eligible RCTs were analyzed. Enzalutamide, apalutamide and darolutamide were more effective than bicalutamide in treating CRPC, and the performance of darolutamide was slightly worse than the other two second-generation ARIs. Similar adverse events rate were observed among the second-generation ARIs and bicalutamide. Apalutamide showed a slightly higher rate of Grade 3+ AEs, percentages of AE-related drug withdrawals and AE-related mortality. Patients receiving enzalutamide had significantly higher rate of hypertension and fatigue. In subgroup analysis, enzalutamide showed better therapeutic effects compared with bicalutamide in both nmCRPC and mCRPC groups. In nmCRPC group, enzalutamide and apalutamide had more benefits on PFS and PSA-PFS compared with darolutamide. We displayed the probability ranking map of PFS, PSA-PFS, OS, time to cytotoxic chemotherapy, PSA response rate and relative AE outcomes. Conclusion: The current network meta-analysis indicated that the second-generation ARIs were superior to the conventional ARI, bicalutamide. The three second-generation ARIs showed incomplete equivalence on CRPC treatment. The darolutamide was slightly less effective compared with enzalutamide and apalutamide. The adverse events of apalutamide were worse than the others, but no statistical significance was observed among these vital AEs. All ARIs were generally well-tolerated. These results may provide reference to clinical decision and further direct comparison trials.